Islamic Fashion and Anti-Fashion: New Perspectives from Europe and North America By Emma Tarlo and Annelies Moors, eds. (London and New York: Harvard, Bloomsbury Academic, 2013. 294 pages.) (American Journal of Islam and Society, 2015)
This volume of scholarship surrounding Islamic fashion presents a counternarrativeto a dominant story: that Muslim women in the West are subjugatedby the oppressive and patriarchal yoke of Islam. Islamic Fashion and Anti-Fashion: New Perspectives from Europe and North America offers a freshnew look at veiling, its intersection with religious piety, family, community,religious authority, fashion, and commoditization through sixteen distinct stud-104 The American Journal of Islamic Social Sciences 32:2ies ranging from clothing items like the burqini and the pardosu to larger issuessurrounding identity and politics, such as North American Islamophobia andits impact on Canadian Muslims. This book represents a large field of researchon Muslim women’s lived experiences, one that reveals the complexities inherentin these religious actors whose choices of dress reveal a large set ofcompeting values, desires, and commitments.The book is organized into five sections: location and encounter, historyand heritage, the marketplace, fashion and media, and fashion and anti-fashion.Two of its attractive features are the numerous black and white images runningthrough many of the chapters, as well as the two groups of stunning, provocativecolor photographs showing the richness of Islamic fashion, from “hijabistreet style” to London Muslim hipster style ...